Effect Of Polypropylene Fiber On The Properties Of Mortar Containing Silica Fume - Apilin, Nur Shuhada (Universiti Sains Malaysia, 2017)
An investigation has been performed to study the effect of polypropylene fiber on the properties of mortar containing silica fume. The experiment consists of testing of fresh mortar via flow table test, as well as hardened mortar such as compressive strength, flexural strength, ultrasonic pulse velocity (UPV), porosity, water absorption and gas permeability test. Plastic shrinkage cracking was also studied in this project using a specially fabricated mould and observed after 24 hours. Mortar sample with characteristic strength of 50 N/mm2 was designed and tested at 7, 14 and 28 age days. Silica fume content used was 10% and polypropylene fiber volume fraction was 0.1%, 0.3% and 0.5%. The control mix was the mortar containing silica fume with no fiber. Based on the compressive strength result, the addition of fiber did not give positive impact on the compressive strength. The fiber addition also has no significant influence on the flexural strength of the mortars. The pore structure in the specimens increased due to the additional of fiber in the mortar. Permeability and porosity of the mortars increased due to the increase volume of fiber fraction but decreased with longer curing periods. The quality of specimens fall in the range of good quality. However, the combination of 10% of silica fume and 0.3% fiber results in optimum mixture design.